Effective Teacher Training in Low-Income Countries : The Power of Observational Learning Research - Abadzi, Helen (World Bank, Washington, DC, 2017)
The Education for All (EFA) initiative depends on students being taught by suitably and sufficiently trained teachers. But time-on-task studies conducted in low-income countries show that relatively little time is being spent on instruction, including the critical teaching of reading. Teachers may be absent often and may avoid teaching when in school (Abadzi 2007). They may engage with the few students who can do the work, neglecting the rest (Llambiri 2006, Abadzi and Llambiri 2011). They may fail to use textbooks even when they exist and spend class time copying on the blackboard. The same issues affect supervisors and principals (Abadzi 2006). As a result, students may graduate or drop out illiterate. The investments in teacher training are potentially valuable, but need to be linked to results. Thus far evidence is limited. Preservice training often lasts 6-9 months compared to 3-4 years in higher-income countries and may be insufficient to remedy students' academic deficits or teach them how to teach. The poor results have disappointed governments and donors. The persistent teacher training problems worldwide make it imperative to seek new means for changing behaviors, particularly for poorly paid teachers with limited education. This must be done relatively quickly and efficiently so that teachers can impart basic skills to their students. Since feasible educational methods seem to have been exhausted, it is useful to look for solutions in the field that studies behavior. Even for better educated teachers in lower-income countries, the capacity for formulating and solving complex problems such as those presented in teaching real classrooms may be limited compared to some 'ideal' model (Feldon 2007).